Comutação resistiva por filamentos verticais em filmes finos de ZnO - Melo, Adolfo Henrique Nunes (2016)
The resistive random access memories (ReRAM) are a class of emerging devices of the new generation of non-volatile memories. Many researchers have been providing many efforts to understand and develop these new memories by presenting simple metal-insulator-metal structure (MIM), easy of read / write, high storage density and low power consumption. The resistive switching (RS) is the basic phenomenon for the functioning of these memories, in which when a given voltage is applied to the MIM device, it may suffer the switching from initial insulating resistance state (HRS - High Resistance State) to a conductor resistance state (LRS - Low resistance state). The RS has been observed in various materials such as ZnO, NiO, perovskites and some solid electrolyte, in which two typical behaviors were observed: unipolar and bipolar. The unipolar switching behavior is independent of the applied polarity, while the bipolar behavior is not dependent. However, the influence of the insulating medium at kind behavior has not been known yet or how the insulating properties of the crystal may favor one or other behavior kind. Thus, in this study were constructed devices with structure Pt/ZnO(t)/ITO and Pt/ZnO(t)/Pt on glass substrates, where t is the deposition time of the ZnO layer varing from 3 min to 3 h. XRD measurements were performed showing that the crystallinity of the samples increased with the deposition time t > 30 min, however, the devices with t < 30 min no diffraction peak was observed. The RS behavior of all devices indicated that the switching from HRS to LRS was given by creation of conducting filaments based on oxygen vacancies, connecting the electrodes. It was observed that there was no significant influence of the lower electrode from the value of the filament forming voltage. In all devices the process of destruction of the filaments was based on the Joule effect, in which the conductive path is permanently destroyed that caused structural damage inside the ZnO matrix. The analyses showed that the behavior of RS was quality dependent of ZnO matrix, where appropriate values of oxygen vacancies are necessary for better performance in resistive memory.